To the issue of cooperation project between Imperial Russian State Papers Manufactory and Partnership of Typography «A. A. Levenson» during the First World War - A. P. Balachenkova; D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The paper deals with the problems of banknote production of the Imperial Russian State Papers Manufactory (hereinafter — Manufactory) during the First World War. The purpose of the work is to provide information about the project of cooperation between Manufactory and the Partnership of Typography «A. A. Levenson» that arose in wartime circumstances. The relevance of the work is seen from the fact that the issues not reflected in historiography. The study will provide more complete and clear picture of the Russian banknote production during the First World War; the solutions to the crisis of the industry and the role of prominent printer S. S. Ermolaev in this process. Unpublished sources from the Central State Historical Archive of St. Petersburg (hereinafter — CSHA St. P) served as the basis for preparing the work